The role of nutrition in the preventive treatment and etiopathogenesis of breast cancer - Eliza Wołoszynek; Katarzyna Maj–Gnat; Jolanta Stępnik; Renata de Pourbaix (Journal of Education, Health and Sport, 2019)
The incidence of cancers is rising worldwide Breast cancer is a cancer whose incidence is steadily increasing in the many countries. In women, breast cancer is the most common malignancy whilst its morbidity rates are the second most frequent after lung cancer. A large body of evidence indicates that about one fourth of breast cancer cases are connected with an unhealthy diet, and pro-health lifestyle can result in even 50% of reduction of breast cancer risk. Inappropriate nutrition and dietary habits are a direct cause or a risk factor of many neoplastic diseases – including breast cancer. A change of these habits can significantly contribute to reducing the risk of breast cancer.